Curriculum greening in higher education: na integrative review of the literature (Research, Society and Development, 2020)
The objective is to investigate, through an integrative review, the international and national discussion of curriculum greening in the higher education. Criterious searches were made in four scientific bases and in the Biblioteca Digital Brasileira de Teses e Dissertações (BDTD), and 33 documents were selected. The analysis includes the language, the publication year, sources of documents, the research área and qualitative information through the grouping of the results in four analytical categories. The analysed studies show the necessity toadvance in the curriculum greening proposal, specially, the teacher training in which contents and practices towards the sustainability are the main focus. Such training must work in the curriculum construction and in the use of methodologies that offer interdisciplinary practices.